Analysis of the Determinants of Open Unemployment and Poverty Rates in East Java Province - Natasya Nur Fadila; Kukuh Arisetyawan (Jurnal Ilmu Ekonomi JIE, 2026)
The purpose of this study is to analyze the simultaneous and partial influences of the labor force participation rate, human development index, district/city minimum wage, per capita expenditure, and technology on the open rate and poverty in the regencies/cities of East Java Province for the period 2020-2024. Using a quantitative approach with multivariate analysis and multiple and simple regression. Data obtained from the Central Statistics Agency. The results show that the labor force participation rate, human development index, district/city minimum wage, per capita expenditure, and technology simultaneously influence the open unemployment rate, which ultimately also affects poverty in the regencies/cities of East Java Province.